Assessment of the bioprotective potential of lactic acid bacteria against Listeria monocytogenes on vacuum-packed cold-smoked salmon stored at 8 °C. (October 2019) - Aymerich, Teresa; Rodríguez, Maria; Garriga, Margarita; Bover-Cid, Sara
Abstract: Smoked salmon is a highly appreciated delicatessen product. Nevertheless, this ready-to-eat (RTE) product is considered at risk for Listeria monocytogenes, due to both the prevalence and growth potential of this bacteria on the product. Biopreservation may be considered a mild and natural effective strategy for minimizing this risk. In this study, we evaluated the following three potential bioprotective lactic acid bacterial strains against L. monocytogenes in three smoked salmon types with different physicochemical characteristics, primarily fat, moisture, phenol and acid acetic content: two bacteriocin-like producers that were isolated from smoked salmon and identified as Lactobacillus curvatus and Carnobacterium maltaromaticum and a recognized bioprotective bacteriocin producer from meat origin, Lactobacillus sakei CTC494. L. sakei CTC494 inhibited the growth of L. monocytogenes after 21 days of storage at 8 °C in all the products tested, whereas L. curvatus CTC1742 only limited the growth of the pathogen (<2 log increase). The effectiveness of C. maltaromaticum CTC1741 was dependent on the product type; this strain limited the growth of the pathogen in only one smoked salmon type. These results suggest that the meat-borne starter culture, L. sakei CTC494, may potentially be used as a bioprotective culture to improve the food safety of cold-smoked salmon. Highlights: L. sakei CTC494 exerted a listeriostatic effect on cold-smoked salmon. L. curvatus CTC1741 limited the growth of L. monocytogenes on cold-smoked salmon. C. maltaromaticum CTC1742 exhibited listericidal activity only in vitro. The antilisterial effect of the Lactobacillus did not depend on the cold-smoked salmon type.